Prevalence of dental trauma in patients with cerebral palsy - De Moraes Costa, Mariana MacHado Teixeira [UNESP]; Afonso, Rebeca Lima [UNESP]; Ruviére, Denise Belucio [UNESP]; Aguiar, Sandra Maria Herondina Coelho Ávila de [UNESP] (Wiley, 2008)
This study presents the findings of a record review that evaluated the prevalence of dental trauma in patients with cerebral palsy and evaluated its possible relationship with age, type of palsy, and epilepsy. The dental records of 2,200 patients with special needs admitted to the special care clinic of the School of Dentistry of Araçatuba/UNESP, Brazil, between 1998 and 2003 were reviewed. Of the records that were analyzed, 500 patients who had cerebral palsy were selected for this study. Information regarding age, gender, type of palsy and dental trauma was collected and statistically analyzed. It was observed that 10.6% of the subjects (n = 53) had sustained dental trauma. The number of traumatized teeth was 84. Enamel or enamel/dentin fractures were the most frequent types of traumatic injury (84.9%). The permanent maxillary central incisors were the most commonly affected teeth (50%). The frequency of traumatic injuries showed no significant correlation (p>.05) with the type of cerebral palsy or gender and they were more frequent in subjects between the ages of 0 and 12 years. Having epilepsy was not a statistically significant risk factor (p>.05) for dental trauma. © 2008 Special Care Dentistry.
Keywords: Cerebral palsy; Dental fracture; Epilepsy; adolescent; adult; cerebral palsy; child; female; human; incisor; infant; injury; male; maxilla; preschool child; retrospective study; tooth injury; Adolescent; Adult; Cerebral Palsy; Child; Child, Preschool; Female; Humans; Incisor; Infant; Male; Maxilla; Retrospective Studies; Tooth Injuries